Design and Development of a Line-Following Automatic Guided Vehicle (AGV) Model as a Food and Beverage Delivery Platform - Luqyana, Dhiya; Putri, Nuke Earlyana; Muslimin, Muslimin; Milah Muhamad, Azam (Jurnal Mekanik Terapan, 2026)
An Automatic Guided Vehicle (AGV) is an automated vehicle used to support the delivery of food and beverages in restaurant service systems, where manual methods still carry risks of delays and spillage. This study designs and builds a line-following AGV using a Quality Function Deployment (QFD) approach with screening and scoring concepts to translate user needs into the technical specifications of the device. The research stages include needs identification, mechanical and electronic design, Arduino programming, and track testing. The AGV is capable of following a path with high accuracy using infrared sensors, automatically stopping at the destination, and detecting obstacles via ultrasonic sensors, with a buzzer serving as a delivery indicator. Test results show stable delivery performance with a relatively low spillage rate of 10%–13.33%. The AGV measures 40 × 30 × 43.6 cm, uses a 12 V battery, two DC motors, has a speed of 0.25 m/s, a maximum load capacity of 2 kg, and is controlled by an Arduino Uno with an integrated sensor system.